Controle Et Performance Des Reseaux De Pme Camerounaises : Une Approche Transactionnelle - Tcheubeu Nana Tyéri B.; Ngomesse Njike Désirée (European Scientific Journal, ESJ, 2017)
Nowadays, companies, and especially SMEs, are engaged in fierce competition. One of the solutions to this strong competition is for these companies to reduce the number of potential suppliers and to establish strategic partnership relationships. This is how a networked organization allows them to be more flexible and better able to adapt to this environment. Research, however, reveals a very weak life experience of business networks. The objectives of this work are to present the control in the transactional approach within SME networks, to check whether it can explain the performance of these SMEs. From an observation of 54 Cameroonian SMEs in the manufacturing and logistics sectors, it is clear that among the tools of the transactional control mode, contracts less than six months are the most used and these negatively influence the performance of network SMEs. This important use of contracts of less than six months may be due to non-compliance with the terms of the contract by the partners, legal and judicial insecurity which leads the partners to evaluate first the performance of a contract less than six months, before moving on to another contract.